Highly Pathogenic Avian Influenza H5N8 in Germany: Outbreak Investigations. Issue 1 (30th October 2015) - Conraths, F. J.; Sauter‐Louis, C.; Globig, A.; Dietze, K.; Pannwitz, G.; Albrecht, K.; Höreth‐Böntgen, D.; Beer, M.; Staubach, C.; Homeier‐Bachmann, T.
Summary: Epidemiological outbreak investigations were conducted in highly pathogenic avian influenza virus of the subtype H5N8 (HPAIV H5N8)‐affected poultry holdings and a zoo to identify potential routes of entry of the pathogen via water, feedstuffs, animals, people, bedding material, other fomites (equipment, vehicles etc.) and the presence of wild birds near affected holdings. Indirect introduction of HPAIV H5N8 via material contaminated by infected wild bird seems the most reasonable explanation for the observed outbreak series in three commercial holdings in Mecklenburg‐Western Pomerania and Lower Saxony, while direct contact to infected wild birds may have led to outbreaks in a zoo in Rostock and in two small free‐range holdings in Anklam, Mecklenburg‐Western Pomerania.